2022
DOI: 10.3390/su141710813
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Practices and (Post) Pandemic Consumption of Private Labels: Online and Offline Retail Perspective in a Portuguese Context

Abstract: Currently, given the different dynamics of competition, food retailers are increasingly betting on private labels as a strategy of differentiation and retention of competitive advantages. To this extent, this study aims to assess the antecedents of the purchase intention of food retailers’ private labels, as well as to understand the managerial practices and (post) pandemic consumption retail perspective in a Portuguese context. The results obtained, through a quantitative analysis by means of multiple linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…This study also contributes to the discussion on the impact of brand trust on customer loyalty. While some studies suggest that the impact of brand trust on loyalty may not be straightforward (Chen et al ., 2009), our findings emphasize that this relationship may be moderated by specific contexts, including sectors with high competition (Pinto et al ., 2022; Ruiz-Molina et al ., 2017; Loureiro et al ., 2014; Nesset et al ., 2021) and high levels brand trust towards the major players in the industry (Loureiro et al ., 2014).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study also contributes to the discussion on the impact of brand trust on customer loyalty. While some studies suggest that the impact of brand trust on loyalty may not be straightforward (Chen et al ., 2009), our findings emphasize that this relationship may be moderated by specific contexts, including sectors with high competition (Pinto et al ., 2022; Ruiz-Molina et al ., 2017; Loureiro et al ., 2014; Nesset et al ., 2021) and high levels brand trust towards the major players in the industry (Loureiro et al ., 2014).…”
Section: Discussionsupporting
confidence: 60%
“…The current study highlighted the important role of sustainability practices in the retail industry. Food retail is marked by intense rivalry (Pinto et al ., 2022; Ruiz-Molina et al ., 2017; Loureiro et al ., 2014) and major efforts in loyalty programs (Bies et al ., 2021; Steinhoff and Zondag, 2021; Nesset et al ., 2021). In such a demanding context, this article provides valuable insights for retail managers, as it demonstrates that integrating sustainability in operational activities such as the types of products (pre-packaged and packaging-free) that are available in stores can help foster customer loyalty.…”
Section: Discussionmentioning
confidence: 99%
“…Pinto et al (2022) found that customers showed high satisfaction and loyalty towards PL brands, revealing that the purchase experience, the image of PLs, perceived risk, and the impact of the pandemic influenced customers' attitudes and intentions to purchase and recommend PL products. Additionally, due to the pandemic, some consumers shifted their purchasing patterns and increased their consumption of PL products (Pinto et al, 2022). Also, Pinto et al (2022) suggest future studies on factors such as third-party recommendations, the current economic situation, PL packaging, and also comparative studies with other sustainable brands in Portugal or expanding the research to other countries where sustainable PLs are available.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this context, future research should include comparisons in terms of quality and pricing to analyse the development of PLs in organic product categories and the extent to which sustainability is integrated into PL offerings. Pinto et al . (2022) found that customers showed high satisfaction and loyalty towards PL brands, revealing that the purchase experience, the image of PLs, perceived risk, and the impact of the pandemic influenced customers' attitudes and intentions to purchase and recommend PL products.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation